2019
DOI: 10.1177/0192623319863129
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Image Analysis System for the Measurement of Cell Proliferation in Mammary Glands of Rats

Abstract: Reliable detection and measurement of cell proliferation are essential in the preclinical assessment of carcinogenic risk of therapeutics. In this context, the assessment of mitogenic potential on mammary glands is crucial in the preclinical safety evaluation of novel insulins. The existing manual counting is time-consuming and subject to operator bias. To standardize the processes, make it faster, and resistant to errors, we developed a semiautomated image analysis system (CEPA software, which is open-source)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…8,9 Our findings are also in concordance with a recent study in rat mammary gland tissue, where a user-developed software was used for quantification of the Ki67+ LI. 14 In that study, an algorithm was developed for identification of glandular tissue, but the authors describe that this algorithm often misclassified adipose tissue or connective tissue as glandular tissue. Therefore, it was necessary to visually inspect all the classified areas and when needed, manually correct the algorithm classification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Our findings are also in concordance with a recent study in rat mammary gland tissue, where a user-developed software was used for quantification of the Ki67+ LI. 14 In that study, an algorithm was developed for identification of glandular tissue, but the authors describe that this algorithm often misclassified adipose tissue or connective tissue as glandular tissue. Therefore, it was necessary to visually inspect all the classified areas and when needed, manually correct the algorithm classification.…”
Section: Discussionmentioning
confidence: 99%
“…32 Furthermore, in the recent mammary gland study discussed above, it was in fact the area of positive and negative nuclei which was quantified, which subsequently was divided by a constant value for the average area per nucleus. 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, safety studies evaluate changes based on histochemical stains (such as H&E and Masson trichrome), and several studies have demonstrated the feasibility of automated scoring in murine studies of liver fibrosis, 30 , 31 quantification of hepatic lipid droplets and steatosis, 32 , 33 heart ischemic injury, 34 lung fibrosis, 35 , 36 kidney injury, 37 and pancreatic toxicity. 38 Biomarker studies that rely on IHC and QIA have been successfully deployed, for example, to quantify proliferative Ki-67 cells in rodent mammary glands 39 and endometrium 40 to study reproductive toxicity. Other studies have similarly utilized image analysis to examine processes relevant to several pathologies such as caspases in cell death, 41 T-cell and B-cell markers in inflammation, 42 and collagen deposition related to fibrosis.…”
Section: Applications Of Biomarker Imaging Analysismentioning
confidence: 99%
“…If positive nuclear staining is the objective, individual biomarker positive nuclei could be quantified or an average nuclear count could be calculated using biomarker-positive area divided by the average nuclear area. 23…”
Section: Aspects To Consider Before Starting Digital Tissue Image Analysismentioning
confidence: 99%